Targeting Antisense Mitochondrial Noncoding Rnas Induces Bladder Cancer Cell Death and Inhibition of Tumor Growth Through Reduction of Survival and Invasion Factors - Borgna-Christie, V (Ivyspring International Publisher, 2020)
Knockdown of the antisense noncoding mitochondrial RNAs (ASncmtRNAs) induces apoptotic death of several human tumor cell lines, but not normal cells, supporting a selective therapy against different types of cancer. In this work, we evaluated the effects of knockdown of ASncmtRNAs on bladder cancer (BCa). We transfected the BCa cell lines UMUC-3, RT4 and T24 with the specific antisense oligonucleotide Andes-1537S, targeted to the human ASncmtRNAs. Knockdown induced a strong inhibition of cell proliferation and increase in cell death in all three cell lines. As observed in UMUC-3 cells, the treatment triggered apoptosis, evidenced by loss of mitochondrial membrane potential and Annexin V staining, along with activation of procaspase-3 and downregulation of the anti-apoptotic factors survivin and Bcl-xL. Treatment also inhibited cell invasion and spheroid formation together with inhibition of N-cadherin and MMP 11. In vivo treatment of subcutaneous xenograft UMUC-3 tumors in NOD/SCID mice with Andes-1537S induced inhibition of tumor growth as compared to saline control. Similarly, treatment of a high-grade bladder cancer PDX with Andes-1537S resulted in a strong inhibition of tumor growth. Our results suggest that ASncmtRNAs could be potent targets for bladder cancer as adjuvant therapy. © The author(s).